DISPUTE RESOLUTION ON CLASSIFICATION OF IMPORTED GOODS PARAQUAT DICHLORIDE FOR LEGAL CERTAINTY - Enna Budiman; Timbo Mangaranap Sirait; Khalimi (JILPR Journal Indonesia Law and Policy Review, 2025)
The classification dispute over the import of Paraquat Dichloride between an importing company and the Directorate General of Customs and Excise has become an important precedent in Indonesian State Administrative Law (TUN), particularly in the customs sector. The dispute arose due to different interpretations of tariff classification: the importer classified Paraquat 42% Technical as a raw chemical (HS 2933.39.30.00) with a 0% import duty rate, while Customs classified it as a ready-to-use herbicide (HS 3808.93.19.00) with a 5% rate. This dispute had significant implications for the fiscal obligations of both the company and the state, and highlighted regulatory uncertainty in the pesticide industry. This study aims to analyze the dispute resolution mechanism in that context, covering the appeal process at the Tax Court, Judicial Review at the Supreme Court, and the broader implications for legal certainty and administrative practices. The method used is normative juridical with a statutory approach and a case study of court decisions. The analysis found and concluded: First, the administrative dispute resolution mechanism in customs classification follows a tiered process consisting of administrative objection, judicial appeal to the Tax Court, and judicial review (PK) to the Supreme Court. Second, in terms of legal reasoning, both the importer and DJBC presented arguments based on valid legal frameworks, but differed in interpreting the tariff classification, each supported by legally debatable claims. Third, the Tax Court and the Supreme Court assessed the case objectively using evidence such as laboratory analysis results, the Indonesian Customs Tariff Book (BTKI), and fundamental principles of administrative law. Fourth, the legal implications of the Supreme Court's ruling are highly significant for public administration, reinforcing the legal authority of DJBC and potentially serving as jurisprudence in the future.